Determining Transport Characteristics for Cell Plasma Membranes under Extracellular Crystallisation - Kuleshova, L. G.; Kovalenko, I. F. (Problems of Cryobiology and Cryomedicine, 2006)
Experimental proving of theoretical model adequacy, analytically describing processes of transmembrane substance transfer during ice crystal growth in extracellular medium was carried-out in the work. Within the frames of model’s assuming there was obtained a satisfactory fitting of theoretical and experimental dependencies of a change in relative volume of golden hamster kidney cells under different freezing conditions. Transport characteristics of plasma membranes in mentioned cells were quantitatively estimated and the most probable reasons of their dependency on initial concentration of cell penetrative cryoprotectant and cooling rate were analysed.